Formulasi Dan Uji Aktivitas Sediaan Face Mist Ekstrak Etanol Daun Jarak Pagar (Jatropha curcas L.) Sebagai Antikosidan Dengan Metode DPPH - Raru, Preiscylia; Marzuki, Asnah; Alam, Syamsul (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Jarak pagar (Jatropha curcas L.) one as an antioxidant. This research aims to obtain a formulation in the form of a stable face mist dosage form and determine the IC50 value of the extra ethanol face mist preparation from jatropha leaves (Jatropha curcas L.) which has potential as an antioxidant. Experimental research method using 96% ethanol solvent, maceration method. The resulting thick extract is rotated, then preparations are made with concentrations of 0.1%, 0.3% and 0.5%, using additional ingredients glycerin as a humectant, propylene glycol as a humectant, sodium benzoate as a preservative, lavender as a fragrance and distilled water. as a solvent. Evaluation of the preparation, namely the cycling test in 6 cycles for 12 days, organoleptic observations obtained in liquid form, pH measurement results were <0.05p, homogeneity tests obtained homogeneous preparations, Viscosity test results were <0.05p, skin moisture and irritation tests were <0.05p. As well as antioxidant testing using the DPPH method using a UV-Vis spectrophotometer. The results of the research can be concluded that Jatropha curcas L. extract can be formulated as a face mist preparation that is physically and chemically stable. The IC50 values ​​using the facial mist preparation formula of Jatropha curcas (Jatropha curcas L.) leaf extract were respectively 17.0276 ppm, 16.5071 ppm, and 13.4743 ppm. The most effective face mist formulation has the highest antioxidant value in formula III.